(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the issues of threat detection based on artificial intelligence (AI) and ensuring cybersecurity through Zero-Trust architecture in hybrid cloud environments. Due to the inadequacy of traditional security approaches in hybrid infrastructures, it is essential to operate based on the Zero-Trust model, which verifies every access point. AI technologies enable real-time threat prediction, anomaly detection, and rapid response to threats. Furthermore, the article highlights how the components of Zero-Trust architecture, user identity, permission management, and security monitoring integrate with AI. Additionally, through the application of AI and Zero-Trust approaches in hybrid cloud environments, organizations can establish a robust defense system against cyberattacks, automate security policies, and maintain constant monitoring of information systems.